If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8a + 6a + 7 = 1 Reorder the terms: 7 + -8a + 6a = 1 Combine like terms: -8a + 6a = -2a 7 + -2a = 1 Solving 7 + -2a = 1 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2a = 1 + -7 Combine like terms: 7 + -7 = 0 0 + -2a = 1 + -7 -2a = 1 + -7 Combine like terms: 1 + -7 = -6 -2a = -6 Divide each side by '-2'. a = 3 Simplifying a = 3
| F(x)=0.75+80 | | 8t+2-10m-8=20 | | x=-x^3+22x^2+210x+1 | | C(20)=3x+45 | | -5+1=0 | | 9+12=2w+5w | | 9+3n^2=21 | | .04(x)=140 | | 5n+3+5=-25 | | 8m+2n+16r= | | -16x^2+32x+16=0 | | 4x+80=120 | | 65=.5(x).02+.5(y).03 | | 6b+19=5b+7 | | y=-4x^2-2.5 | | 0.45*1/6 | | 4y^2+40y+64= | | 9+4x=3+2x | | 35n^2=6-23n | | z/5=3/4 | | 90=15/2h | | 4(x+14)=60 | | 73/100*(-2/7) | | -3*-1-1=-1+-3 | | 16t+3=0 | | x=32-5t+2t^2 | | https://www.youtube.com/watch?v=UFLWvSRXNl4 | | 5d+2=37 | | z/5=334 | | -2(-6+5x)-1= | | 7(t-3)+7t=7(2t+3)-10 | | x-54/2=32/4 |